A study of economic and domestic activities of rural women in farming household of Brgy. Agcawilan, Lezo, Aklan. - Meñez, Joyce Rose Bautista
The study attempts to find out the economic and domestic activties of rural women in Barangay Agcawilan Lezo, Aklan. The study attempts to answer the following objectives: (1)to describe the domestic activities engaged by married and unmarried rural women in farming household; (2)to describe the economic activities carried out by married and unmarried rural women in a farming household; (3)to determine the diferences in the domestic and economic activities of married an unmarried women., Barangay Agcawilan in the Municipality of Lezo, Aklan was selected fort he study. Women from farming household was selected for the study. Women from farming household aged 20 to 60 years old were the respondents of this study. There 104 of them in all who were interviewed. Interview schedule was used in gathering of data. The results of the study show that rural women regardless of their marital status are engaged in domestic and economic activities. married women are expected to take care of the household chores and at the same time engage in wage earning activities to help augment the income of their family. unmarried ones had lighter tasks; They are not obliged to help their family in terms of income.